PolyMorph: Extension of PolyHoop for tissue morphogenesis coupled to chemical signaling - Nicolas Pascal Guido Müller; Roman Vetter (Computer Physics Communications, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Optimizing laboratory cultures of Gammarus fossarum (Crustacea: Amphipoda) as a study organism in environmental sciences and ecotoxicology - Roman Alther; Andrin Krähenbühl; Pascal Bucher; Florian Altermatt (Science of The Total Environment, 2023)

Low vulnerability of the Mediterranean antipatharian Antipathella subpinnata (Ellis & Solander, 1786) to ocean warming - Godefroid Mathilde; Zeimes Tom; Bramanti Lorenzo; Romans Pascal; Bo Marzia; Toma Margherita; Danis Bruno; Dubois Philippe; Guillaumot Charlène (Ecological Modelling, 2023)

Species and population genomic differentiation in Pocillopora corals (Cnidaria, Hexacorallia) - Didier Aurelle; Marine Pratlong; Nicolas Oury; Anne Haguenauer; Pauline Gélin; Hélène Magalon; Mehdi Adjeroud; Pascal Romans; Jeremie Vidal-Dupiol; Michel Claereboudt; Camille Noûs; Lauric Reynes; et al. (Genetica, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Unveiling asexual reproductive traits in black corals: polyp bail-out in Antipathella subpinnata - Martina Coppari; Lara Fumarola; Lorenzo Bramanti; Pascal Romans; Rémi Pillot; Giorgio Bavestrello; Marzia Bo (Coral Reefs, 2020)
Cnidarians are known to undergo reverse development as a survival mechanism against adverse environmental conditions. Polyp bail-out consists in the polyps’ detachment from the mother colony due to stressful conditions, followed by a complete tissue and cells rearrangement and in some cases in a regression into a simple, ciliated form. Here we describe a massive polyp bail-out event occurred in the mesophotic black coral Antipathella subpinnata in reared conditions. This is the first report of a bail-out event in this species providing new insights into the life cycle and ecology of black corals.

A Marine Biodiversity Observation Network for Genetic Monitoring of Hard-Bottom Communities (ARMS-MBON) - Matthias Obst; Katrina Exter; A. Louise Allcock; Christos Arvanitidis; Alizz Axberg; Maria Bustamante; Ibon Cancio; Diego Carreira-Flores; Eva Chatzinikolaou; Giorgos Chatzigeorgiou; Nathan Chrismas; Melody S. Clark; et al. (Frontiers in Marine Science, 2020)
Marine hard-bottom communities are undergoing severe change under the influence of multiple drivers, notably climate change, extraction of natural resources, pollution and eutrophication, habitat degradation, and invasive species. Monitoring marine biodiversity in such habitats is, however, challenging as it typically involves expensive, non-standardized, and often destructive sampling methods that limit its scalability. Differences in monitoring approaches furthermore hinders inter-comparison among monitoring programs. Here, we announce a Marine Biodiversity Observation Network (MBON) consisting of Autonomous Reef Monitoring Structures (ARMS) with the aim to assess the status and changes in benthic fauna with genomic-based methods, notably DNA metabarcoding, in combination with image-based identifications. This article presents the results of a 30-month pilot phase in which we established an operational and geographically expansive ARMS-MBON. The network currently consists of 20 observatories distributed across European coastal waters and the polar regions, in which 134 ARMS have been deployed to date. Sampling takes place annually, either as short-term deployments during the summer or as long-term deployments starting in spring. The pilot phase was used to establish a common set of standards for field sampling, genetic analysis, data management, and legal compliance, which are presented here. We also tested the potential of ARMS for combining genetic and image-based identification methods in comparative studies of benthic diversity, as well as for detecting non-indigenous species. Results show that ARMS are suitable for monitoring hard-bottom environments as they provide genetic data that can be continuously enriched, re-analyzed, and integrated with conventional data to document benthic community composition and detect non-indigenous species. Finally, we provide guidelines to expand the network and present a sustainability plan as part of the European Marine Biological Resource Centre ( www.embrc.eu ).

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Evaluation of Different Quality-Relevant Aspects of Closed System Transfer Devices (CSTDs) - Ahmed Besheer; Hanns-Christian Mahler; Anja Matter-Schwald; Sergio Mompart Barrenechea; Martin Vogt; Pascal Chalus; Pauline Heymes; Timothy Pillow; Andrea Kirste; Patrick Favrod; Susanne Joerg; Roman Mathaes (Pharmaceutical Research, 2020)

Correction to: In Vivo Stability of Therapeutic Proteins - Joachim Schuster; Atanas Koulov; Hanns-Christian Mahler; Pascal Detampel; Joerg Huwyler; Satish Singh; Roman Mathaes (Pharmaceutical Research, 2020)

In Vivo Stability of Therapeutic Proteins - Joachim Schuster; Atanas Koulov; Hanns-Christian Mahler; Pascal Detampel; Joerg Huwyler; Satish Singh; Roman Mathaes (Pharmaceutical Research, 2020)

Binding of pigments to the cyanobacterial high-light-inducible protein HliC - Mahendra Kumar Shukla; Manuel J. Llansola-Portoles; Martin Tichý; Andrew A. Pascal; Bruno Robert; Roman Sobotka (Photosynthesis Research, 2018)

Executive summary of the 11th HHT international scientific conference - Helen Arthur; Urban Geisthoff; James R. Gossage; Christopher C. W. Hughes; Pascal Lacombe; Mary E. Meek; Paul Oh; Beth L. Roman; Scott O. Trerotola; Sebastiaan Velthuis; Whitney Wooderchak-Donahue (Angiogenesis, 2015)

LC-MS/MS analytical procedure to quantify tris (nonylphenyl)phosphite, as a source of the endocrine disruptors 4-nonylphenols, in food packaging materials - Pascal Mottier; Nancy Frank; Mathieu Dubois; Adrienne Tarres; Thomas Bessaire; Roman Romero; Thierry Delatour (Food Additives & Contaminants: Part A, 2014)

The antidepressant-like effect induced by the sigma1 (σ1) receptor agonist igmesine involves modulation of intracellular calcium mobilization - Alexandre Urani; Pascal Romieu; Elodie Portales-Casamar; François J. Roman; Tangui Maurice (Psychopharmacology, 2002)